The Level of the Trust of Village Youth Communities on the Tourism Bumdes (Village-Owned Enterprises) During the Shock of the Covid-19 Pandemic - Pertiwi, Vi'in Ayu; Pratiwi, Destyana Ellingga; Meitasari, Deny (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2022)
BUMDes is a form of village business developed by the current village government. This village business is the hope of village youth to find work. Many village business entities are engaged in the tourism sector. The Covid-19 pandemic is one of the causes of the decline in the performance of agro-tourism businesses that BUMDes mostly run. The tourism sector has experienced a drastic decline due to government policies to reduce the spread of Covid-19. This condition has an impact on village business units which requires reducing employees. The reduction in the number of employees experienced by BUMDes is the background of this study to analyze the level of trust of village youth in BUMDes as one of the providers of employment in the village. The purpose of the study was to investigate the level of confidence of village youth in the performance of BUMDes. This research was conducted August - October 2021. This study uses a quantitative approach with descriptive statistical analysis. The variable in this study is a single variable, namely trust. The sampling method used is purposive sampling. The research was conducted in BUMDes Raharjo, Bumiaji District, Batu Tourism City, East Java Province, Indonesia. The results showed that the confidence level of village youth was in the medium category. This means that village youth still believe and hope that the existence of BUMDes can empower the surrounding community, especially village youth. Village-owned enterprises can increase youth trust by holding meetings and discussions with village youth. The child must be aware of the potential in their area and together help BUMDes develop village tourism to reduce unemployment.